Arterial stiffness is associated with elastin fragmentation and medial collagen content in the human aorta. (25th November 2020) - Mahmud, A; McNulty, M; McGovern, E; Spiers, J.P; Kavanagh, P; Tolan, M; Young, V; Feely, J; Silke, B
Abstract: Background: Age-related changes in arterial stiffness are ascribed to collagen and elastin content in the aorta (Ao) which is modulated by the matrix metalloprotienases (MMPs). However, no study has directly compared arterial stiffness and arterial structure in man. Methods: Aortic and internal mammary artery (IMA) tissue were obtained from 10 patients (62±1 years, 2 female) undergoing coronary artery bypass grafting (CABG). Aortic pulse wave velocity (PWV) was measured prior to CABG. Collagen content was assessed in tissue sections using Sirius Red staining and elastin by ACCUSTAIN. Elastin fragmentation in the Ao media was graded; increasing in severity from 1 to 4. MMP-2 and MMP-9 activity was quantified in the Ao using gelatine zymography. Results are expressed as mean±SEM, p<0.05 considered significant. Results: The collagen concentration was 50% (intima), 42% (media)and 76% (adventitia) in the Ao but was lower in the IMA. PWV was significantly associated with Ao medial (r=0.79, p=0.03) but not intimal or adventitial collagen concentrations. Aortic intimal thickness was related significantly with age (r=0.70, p<0.05) but not PWV. There was no relationship between age and Ao collagen concentration. There was a significant association (p<0.001) between increasing elastin fragmentation in the aortic media and PWV but not age. There was no relationship between collagen concentration in the IMA and either PWV or age. Neither latent nor active MMP-2 activity was related with PWV or age. Latent MMP-9 expression was significantly associated with PWV (r=0.66, p<0.05) but not age. Conclusions: Our proof-of-concept study is the first one to show that elastin fragmentation in the aorta may underlie arterial stiffening in man. In contrast, the internal mammary artery does not age, unlike the aorta, which makes it the reassuring choice for coronary artery bypass grafting. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Health Research Board, Ireland